Autonomous Fire Extinguisher On The Ship Using Raspberry Pi Pico - Salman Al Farizi; Edi Kurniawan; Henna Nurdiansari; Dirhamsyah Dirhamsyah (Jurnal Ilmiah Teknik Informatika dan Komunikasi, 2025)
Autonomous Fire Extinguisher (AFE) On The Ship or known as an automatic fire extinguisher on a ship is a fire extinguisher without a crew in it in the form of a ship prototype. The fire extinguisher is controlled automatically using a cellphone remote control. This fire extinguisher can also extinguish fire automatically according to the fire point. The research method used is system design and development. The system is designed with an Infrared Flame Sensor, and ESP8266 Wi-Fi to deploy the ship to the position of the fire point and extinguish the fire automatically. The data obtained will be sent to the application using a Raspberry Pi Pico and hardware design to determine the system architecture, selecting appropriate components, software design to develop algorithms and programs, as well as testing and evaluation to assess overall system performance. Data collection techniques are carried out through system testing to evaluate the performance of the component system and the integration of the entire system. The test results show that the Infrared Flame Sensor can detect fire points at a distance of 40cm to 80cm and the active and focused sprayer control system can extinguish according to the accuracy of the fire point (fire) automatically. The results of this test are used to ensure that each component functions according to the specifications that have been given, develop simple tools to be more effective, efficient and improve technology.